Attitudes and usage of thermocoagulation in Sarawak. Same-day high-risk human papillomavirus (hrHPV) testing and thermoablation in early detection and treatment of cervical pre-cancer: A case series - Abigail Rembui, Jerip; DP, Michael; Noor Tini, Sidik; EB, Atin; R, Kaur; Tan, Cheng Siang; Yee, Yee Kyaing (Malaysian Medical Association (MMA), 2024)
AR Jerip1 1 , DP Michael2 , NT Sidek1 , EB Atin2 , R Kaur2 , CS Tan3 , A Idi1 , YY Kyaing1 Department of Obstetrics and Gynaecology, Faculty of Medicine, UNIMAS, Sarawak, Malaysia, 2Long Bedian Health Clinic, Sarawak, Malaysia, 3Department of Tropical and Emerging Diseases, Faculty of Medicine, UNIMAS, Sarawak, Malaysia ABSTRACT Introduction: The WHO now recommends same-day hrHPV screening and thermoablation for cervical pre-cancer screening and treatment. However, robust real-world data is lacking to validate this strategy in remote rural Sarawak. Objective: This study examined the viability of same-day high-risk human papillomavirus (hrHPV) screening and thermoablation treatment for cervical pre-cancer in remote rural Sarawak. Materials and Methods: Through a retrospective case series conducted in Long Bedian, a remote health clinic, we assessed the feasibility of point-of-care testing (POCT) for hrHPV, thermoablation practice and the awareness and attitudes surrounding its usage. Results: Among the 81 recruited women between February 7th and November 19th, 2023 a 12.34% incidence of hrHPV infection was revealed. Most participants (87.65%) tested negative, while 12.34% tested positive for oncogenic HPV types. Acceptance of the same-day screening and treatment protocol was high among both clinic staff and patients. Among hrHPV-positive women, 50% underwent result-day treatment, 40% were referred for further hospital review and 10% defaulted, primarily due to cultural beliefs. No adverse events were reported among those treated, indicating the safety of the procedure. Conclusion: This study highlights the effectiveness, acceptability and safety of the same-day POC testing and result-day treatment strategy in rural Sarawak. These findings support the implementation and expansion of HPV screening and treatment programs to combat cervical cancer in low- and middle-income countries, aligning with WHO recommendations